PENGARUH PERBEDAAN INDIVIDUAL DAN KARAKTERISTIK SISTEM INFORMASI PADA PENERIMAAN PENGGUNAAN TEKNOLOGI INFORMASI DALAM e-library - Lina, Lina (Journal of Indonesian Economy and Business, 2007)
Using the Technology Acceptance Model (TAM) as a theoretical framework, this studyinvestigates the effect of a set of individual differences (computer self-efficacy andknowledge of search domain) and system characteristics (relevance, terminology, andscreen design) on intention to use digital libraries. The aim of this study is to test thecorrelation between perceived ease-of-use variable and perceived usefulness variable,beliefs (perceived ease-of-use and perceived usefulness) against behavior intention to use.This study also to test the relationship between individual differences (computer selfefficacy and knowledge of search domain) and system characteristics, which consist ofrelevance terminology and screen design against belief variables. The study replicatesTechnology Acceptence Model (TAM) by Hong et al (2002) and implements in e-libraryarea. Based on a sample 100 users of a universityâs Gadjah Mada digital library, theresults strongly support the utilization of TAM in predicting usersâ intention to adoptdigital libraries, and demonstrate the effects of critical external variables on behaviorintention through perceived ease of use and perceived usefulness. All of the individualdifferences and system characteristics have significant effects on perceived ease of usedigital libraries. In addition, relevance has strongest effect on perceived usefulness ofdigital libraries.Keywords: Individual differences, system characteristics, Technology Acceptance ModelÂ (TAM) perceived ease-of-use, perceived usefulness, e-library.